Fostering community socio-educational resilience in pandemic times: Its concept, characteristics and prospects - Iglesias, Edgar; Esteban-Guitart, Moises; Puyaltó, Carolina; Montserrat, Carme (Frontiers in Education, 2022)
One area of research that has important implications for preventing school failure is concerned with “resilient students,” or those children and youth learners who succeed in school despite the presence of adverse circumstances. However, this concept supposes a reductionist vision of the phenomenon of educational resilience by considering the individual as an object of intervention, as well as assuming deficits and limitations to it: its socioeconomic, cultural and linguistic condition. In contrast, we understand resilience as an available resource that transcends the individual and is integrated within a given territory, region or city. The aim of this paper is therefore to propose the incorporation of a new term in the available literature, namely, “community socio-educational resilience (CSER),” inspired in the term “community resilience.” To this end, the new term is defined, characterized and illustrated from an experience carried out during lockdown due to COVID-19. By “CSER” we mean the engagement of different social, cultural and educational agents in the design and implementation of creative and transformative educational practices that challenge such adversity and uncertain circumstances as those deriving from the COVID-19 pandemic (i.e., home confinement, remote teaching). Five fundamental dimensions of the construct are proposed and suggestions for educational practice are discussed.